Penilaian Tingkat Kapasitas Adaptasi Terhadap Bencana Banjir Rob Berdasarkan Pengaruh Pembangunan Tanggul Laut Pada Kawasan Pesisir Kota Pekalongan (Studi Kasus: Kecamatan Pekalongan Utara) - Denis Said Mukhtar; Wisnu Pradoto (Jurusan Perencanaan Wilayah dan Kota, 2021)
North Pekalongan district is a coastal area of Pekalongan City which has 7 sub-districts with a high tidal hazard level. Adaptation capacity is a key point in dealing with conditions of vulnerability to climate change, especially tidal floods. The projected threat of tidal flooding which will increase every year has an impact on the survival of the people of the North Pekalongan sub-district. adaptation capacity needs to be increased in order to adapt to exposure to the threat of tidal flooding. The purpose of this study was to assess the level of adaptation capacity of the North Pekalongan sub-district to the threat of tidal hazards. This study uses a quantitative method through the Adaptive Capacity Index (ACI) assessment with the analysis technique of scoring analysis, weighting, and spatial analysis. Assessment of the level of adaptation capacity is seen from the conditions before and after the construction of the embankment. Adaptation capacity, which is a study in this research, is measured through sanitation conditions, access to clean water sources, the existence of educational facilities, the existence of health facilities, the presence of disaster infrastructure, the characteristics of houses, and the level of education. In this study, it was found that there was a change in the level of adaptation capacity caused by the construction of a sea wall in the North Pekalongan District. These changes are aimed at increasing the level of adaptation capacity in Bandengan and Kandang Panjang villages. The conclusion that can be drawn is that the construction of rob handling infrastructure is one of the efforts to increase the adaptation of the government in handling rob disasters.